Electronic structure, growth mechanism and photoluminescence of CaWO4 crystals - Cavalcante, L. S. [UNESP]; Longo, V. M. [UNESP]; Sczancoski, J. C. [UNESP]; Almeida, M. A. P.; Batista, A. A.; Varela, José Arana [UNESP]; Orlandi, Marcelo Ornaghi [UNESP]; Longo, Elson [UNESP]; Li, M. Siu (Royal Soc Chemistry, 2012)
In this paper, aggregated CaWO4 micro-and nanocrystals were synthesized by the co-precipitation method and processed under microwave-assisted hydrothermal/solvothermal conditions (160 degrees C for 30 min). According to the X-ray patterns, all crystals exhibited only the scheelite-type tetragonal structure. The data obtained by the Rietveld refinements revealed that the oxygen atoms occupy different positions in the [WO4] clusters, suggesting the presence of lattice distortions. The crystal shapes as well as its crystallographic orientations were identified by field-emission scanning electron microscopy and high-resolution transmission electron microcopy. Electronic structures of these crystals were evaluated by the first-principles quantum mechanical calculations based on the density functional theory in the B3LYP level. A good correlation was found between the experimental and theoretical Raman and infrared-active modes. A crystal growth mechanism was proposed to explain the morphological evolution. The ultraviolet-visible absorption spectra indicated the existence of intermediary energy levels within the band gap. The highest blue photoluminescence emission, lifetime and quantum yield were observed for the nanocrystals processed in the microwave-assisted solvothermal method.